2021
DOI: 10.1093/sleep/zsab084
|View full text |Cite
|
Sign up to set email alerts
|

After-discharge in the upper airway muscle genioglossus following brief hypoxia

Abstract: Study Objectives Genioglossus after-discharge is thought to protect against pharyngeal collapse by minimising periods of low upper airway muscle activity. How genioglossus after-discharge occurs and which single motor units (SMUs) are responsible for the phenomenon are unknown. The aim of this study was to investigate genioglossal after-discharge. Methods During wakefulness, after-discharge was elicited 8-12 times in healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Data from the placebo session in these participants have been reported in a recent publication (Avraam et al, 2021) (Nicholas et al, 2010;Vecchio et al, 2010;Wilkinson et al, 2008Wilkinson et al, , 2010Woods et al, 2015). Transition of units between IP and IT units is common (Nicholas et al, 2010;Wilkinson et al, 2010), and likewise conversion of EP/ET to TT and vice versa have been observed (Nicholas et al, 2010).…”
Section: Participantsmentioning
confidence: 82%
See 3 more Smart Citations
“…Data from the placebo session in these participants have been reported in a recent publication (Avraam et al, 2021) (Nicholas et al, 2010;Vecchio et al, 2010;Wilkinson et al, 2008Wilkinson et al, , 2010Woods et al, 2015). Transition of units between IP and IT units is common (Nicholas et al, 2010;Wilkinson et al, 2010), and likewise conversion of EP/ET to TT and vice versa have been observed (Nicholas et al, 2010).…”
Section: Participantsmentioning
confidence: 82%
“…Participants were not informed as to which experimental session was which, but most were able to correctly identify the alcohol from placebo session. Data from the placebo session in these participants have been reported in a recent publication (Avraam et al., 2021). Participants were between 19 and 35 years old, had regular sleep patterns (waking regularly between 07.00 and 10.00 h) with good self‐reported sleep quality and did not smoke or take medications (except the oral contraceptive pill).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The administration of a selective agonist for the new excitatory receptor increased the genioglossus tonic electromyographic activity greater than six-fold compared with baseline. There are several steps to be taken in order to apply DREADDs and chemogenetic techniques to humans with OSA; however, these procedures represent to date the most targeted attempt to treat OSA with medications and hold great potential for the future of the field [89].…”
Section: Pharmacological Interventionsmentioning
confidence: 99%